The Efforts of Islamic Religious Education Teachers in Improving Students' Understanding of Religious Tolerance Attitudes - Afrijal, M.; Khairuddin, Khairuddin; Missouri, Randitha (Journal of Instructional and Development Researches, 2025)
This study aims to analyze the efforts of Islamic Religious Education teachers at SMA 4 Kota Bima in enhancing students' understanding of religious tolerance attitudes. The results of the study show that teachers successfully fostered an understanding of religious tolerance through an approach that involved both theoretical teaching in the classroom and direct examples in daily life. The teachers provided concrete examples, such as asking non-Muslim students to respect the worship activities of Muslim students and creating an atmosphere of mutual respect among students. This approach has proven effective in strengthening tolerance attitudes among students. The findings emphasize that religious tolerance education requires not only theoretical teaching but also the application of these values in daily practice. This study contributes significantly to the development of an Islamic Religious Education curriculum that focuses more on character building and appreciation of religious differences in society.